PENERAPAN GOOD CORPORATE GOVERNANCE DALAM PENGELOLAAN YAYASAN DI KOTA PEKANBARU - Wita Ananda Chikita; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Foundation Law Number 16 Year 2001 regulates the existence of a Supervisory or Supervisory Agency in a Foundation, which is internal to the Foundation itself. Being able to run a foundation properly is certainly the success of the coaches, administrators and supervisors in carrying out their respective duties and authorities. Of course the coach plays a big role in the progress of a foundation, because apart from being the highest organ in the foundation, the coach also has a big enough task in the foundation. If the Management commits a violation and results in a loss for the Foundation, then the Trustee has the authority to follow up on the Management.This research uses a typology of sociological legal research or what is also called non-doctrinal legal research, which deals more specifically with legal effectiveness. In this study the authors use descriptive research characteristics, sociological legal research is research carried out directly in the location or in the field to obtain data to provide a complete and clear picture of the problem under study, this research was conducted at five foundations in Pekanbaru City, namely the Foundation. Ilham Orphanage, Ash-Showah Orphanage Foundation, Ar-Rahim Orphanage Foundation, Al-Akbar Orphanage Foundation, and Aisiyyah Orphanage Foundation. From this research, it was found that the implementation of Good Corporate Governance in the regulations regarding the establishment of a Foundation in Pekanbaru City, and how the implementation of Good Corporate Governance in the management of the Foundation in Pekanbaru CityThus, the realization of the implementation of GCG in the establishment of a foundation can be established in the manner stipulated by the Foundation Law. In Article 9 paragraph (1) it is stipulated that a foundation can be established by one or more persons by separating the assets of the founder as initial assets, this provision indicates that the establishment of a foundation is not based on an agreement, first it should be established in accordance with the principles of GCG and in accordance with The Foundation Law which regulates, furthermore, the implementation of GCG in the management of the foundation should be in accordance with the placement of the principles of balance in the Foundation starting from the roles of Foundation organs, and also the application of the Foundation's relationship to the parties, in avoiding conflicts that have often occurred in between the parties in it, as well as the placement of the burden of responsibility, according to the objectives of the foundation as stated in Article 1 paragraph (1) of Law Number 16 of 2001.Keywords: Implementation- Good Corporate Governance - foundation